(untitled) (Global Journal of Human-Social Science, 2024)
This research paper delves into the pervasive discrimination faced by domestic workers within their work environments with a specific focus on the context of Lima Peru The primary objective is to examine the labour conditions of paid domestic workers and explore the potential role of domestic workers unions in addressing these issues Drawing upon a comprehensive review of secondary sources including surveys theses and relevant articles both quantitative and qualitative data are analysed to understand the complexities of the situation Conceptual frameworks such as Human Capabilities Good Living and Intersectionality are utilized to provide a nuanced understanding of the challenges faced by domestic workers The paper is structured into four main sections Firstly the context of the case is presented through secondary sources highlighting the prevalence of informality low wages and asymmetrical power relations Secondly a synthesis of existing literature sheds light on the multifaceted nature of discrimination and labour exploitation within this sector Thirdly the discussion delves into the intersectional dynamics of gender class and ethnicity elucidating how these factors compound the vulnerability of domestic workers The findings underscore the urgent need for policy interventions and union action to address the systemic injustices faced by domestic workers Recommendations are provided for future research and policy development aimed at improving labour conditions and combating discrimination within this marginalized workforce In conclusion this paper contributes to a deeper understanding of the challenges faced by domestic workers in Peru and emphasizes the importance of collective action and policy reform in ensuring their rights and dignity in the workplace